Women in Law Enforcement and Police Use of Deadly Force. Issue 3 (4th May 2019) - Deller, Camille; Deller, Steven C.
Abstract: We test the hypothesis that law enforcement agencies that have a larger share of female officers should experience lower rates of police use of deadly force. We use the Law Enforcement Management and Administrative Statistics 2013 survey of police and sheriff departments ( N = 1, 983). We measure police-involved violence as the number of civilians killed by law enforcement officers from 2013 through 2015 as reported by the website Mapping Police Violence. Using a variety of empirical estimators to take into consideration the structure of the distribution of police-caused deaths, we find consistent results that a higher share of female officers is associated with a higher likelihood of police-caused deaths. These results are consistent with prior findings within the literature and implies that in order to "fit in" with their male counterparts female officers will use coercive tactics to the same extent.